Нанокомпозит ПММ-Ag0 для колориметрического определения глюкозы глюкозооксидазным методом - Брагина, Софья Константиновна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
In the present study, we present a colorimetric nanosensor based on a polymethacrylate matrix with immobilized Ag NPs for glucose determination by the glucose oxidase method. To evaluate the applicability of the nanosensor, determination of glucose in in human serum samples was performed according to the developed procedure.